ANALISIS PENGARUH KEBIJAKAN KERJA DARI RUMAH SELAMA PANDEMI COVID19 TERHADAP KINERJA KARYAWAN - Febrianto , Conradus Rian Wahyu Aji; Ekowati , Dhiana; Nawarcono , Winanto (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
In recent years, the world has been busy with the emergence of the Covid-19 virus. As a result, there are many obstacles faced by the community in carrying out their daily lives, especially regarding work problems. The Covid-19 pandemic has caused the government to implement policies to carry out social distancing and require following health protocols, one of which is working from home. This policy has an impact on the performance of employees who usually work in the office to work from home. This study focuses on how much influence the variables of work information, discipline, environment, and motivation have on employee performance. This study uses a quantitative descriptive method, namely the data collection technique using a questionnaire. The data in this study were 60 respondents, multiple linear regression data processing techniques used SPSS 18. Adjusted R Square test results were 16%. The value of the t test on the work information variable is 1.292, the work discipline variable is 0.175, the work environment variable is 2.692, the work motivation variable is 2.419. The results of this study conclude that the work information variable has an effect on employee performance. The work discipline variable has no effect on employee performance. Work environment variables affect employee performance, and work motivation variables affect employee performance. With the results of this study, it is necessary to concentrate on work discipline to improve employee performance.